Correlating picosecond electron transfer and confined water dynamics in Prussian Blue using electrochemical two-dimensional infrared spectroscopy - Nicholas H. C. Lewis; Anuj K. Pennathur; Andrei Tokmakoff (Proceedings of the National Academy of Sciences, 2026)
Prussian Blue is not only the oldest synthetic pigment, but also an electrochemically active material with modern technological relevance for its electrochromic properties and applications in energy storage. In this work, we study the fundamental mechanism of electron transport processes in this material, and how it varies as the material is progressively oxidized from Prussian White to Prussian Blue. Recently developed methods in spectroelectrochemical ultrafast 2D infrared spectroscopy allow us to measure the electron transfer rate within a film of Prussian Blue deposited onto the working electrode in an electrochemical cell as a function of applied bias potential. The intrinsic CN stretching modes serve as a local probe of the Fe oxidation state and as a measure for the solvation dynamics induced by water molecules incorporated into the subcells of the zeolitic lattice. We observe a fast, ps-scale electron transfer process with a rate that varies with the state of the material, revealing the intrinsic mobility of electrons decoupled from the slow diffusion of K+ ions. By correlating these observations to changes in the local structural distributions of FeIII sites, K+ ions and water molecules with the aid of a lattice model, we obtain insight into the mechanism of electron transport in this material. These results demonstrate a method for observing fast electron transfer and correlating them with nuclear motions, and provide a way to study chemical transformations at the electrochemical interface.